Factors associated with hepatitis C and HIV testing uptake among men who inject image and performance enhancing drugs. (8th November 2020) - Hope, Vivian D.; McVeigh, James; Begley, Emma; Glass, Rachel; Edmundson, Claire; Heinsbroek, Ellen; Kean, Joseph; Campbell, John; Whitfield, Mark; Morgan, Gareth; Acreman, Dean; Smith, Josie
Abstract: Introduction and Aims: Historically, people who inject image and performance enhancing drugs (IPED) were not perceived as being at high risk of HIV or hepatitis C virus (HCV) infection. However, recent studies indicate HCV and HIV prevalences are elevated, with many HCV infections undiagnosed. Design and Methods: Men who inject IPEDs recruited from community settings and specialist services, including needle‐syringe programs, across UK during 2016 self‐completed a questionnaire. Multivariate analyses examined factors associated with HCV/HIV testing. Results: The participants' ( n =562; 24% service recruited) median age was 31 years, 4% identified as gay or bisexual, 18% had ever been imprisoned and 6% had ever injected a psychoactive drug. Those community recruited more often reported sharing drugs vials (16% vs. 8%, P =0.021) and, among those with 2+ sexual partners, poor condom use (50% vs. 36%, P =0.063), than those service recruited. Overall, one‐third had ever been tested for HCV (31%) and/or HIV (34%). Testing uptake was associated with other risk factors for HCV/HIV, being recruited through services and having received metabolic tests. Participants' motivations for using IPEDs were associated with recruitment setting and HIV/HCV testing uptake. Discussion and Conclusions: The majority were untested for HCV/HIV. HCV/HIV testing and risks were associated with recruitment through services. Previous needle and syringe program‐based studies have potentially overestimated testing uptake and underestimated risk. Targeted interventions are needed, particularly for those not accessing services. The association between HCV/HIV testing uptake and receipt of metabolic tests suggests that developing a combined offer of these tests as part of health monitoring could improve uptake.